Regulation of colon injury and improvement of exercise performance in exhausted running mice by Lactobacillus pentosus CQZC02 - Cai, Limin; Wang, Beibei (Frontiers in Physiology, 2024)
In this study, strenuous forced exercise caused intestinal damage and reduced the exercise capacity of mice. However, the antioxidant and anti-inflammatory properties of Lactobacillus pentosus CQZC02 (LPCQZC02) were found to improve both the intestinal barrier and exercise function in mice. The effectiveness of LPCQZC02 was confirmed through various methods, including kit detection, pathological observation, quantitative reverse transcription polymerase chain reaction (qRT-PCR), and intestinal flora analysis. The findings demonstrated that LPCQZC02 could control colonic index, lessen colonic enlargement caused by intense exercise, and extend the running duration of mice. Serum levels of total superoxide dismutase (T-SOD), glutathione (GSH), and interleukin-10 (IL-10) were elevated, whereas those of malondialdehyde (MDA), interleukin-6 (IL-6), and tumor necrosis factoralpha (TNF-α) were reduced. The findings of the mRNA expression analysis revealed that in the colons of mice who remarkably exercised, LPCQZC02 could increase the expression levels of zonula occludens-1 (ZO-1), occludin-1, and claudin-1 genes. Additionally, in skeletal muscle tissue, it could downregulate TNF-α expression level and upregulate copper/zinc superoxide dismutase (Cu/Zn-SOD) and manganese superoxide dismutase (Mn-SOD) expression levels. Furthermore, LPCQZC02 could both reduce and promote beneficial bacteria in the intestines of mice undergoing intense exercise. In conclusion, LPCQZC02 emerged as a functional probiotic and demonstrated a notable advantage over sulfasalazine, a medication for intestinal conditions, in mitigating oxidative inflammation, repairing intestinal barrier damage, and enhancing motor function in mice subjected to strenuous exercise.